How Tiger got his stripes : a folktale from Vietnam - Cleveland, Rob, 1955-; Hoffmire, Baird, 1969- (Atlanta, Ga. : August House Story Cove, 2006)
A little man tricks the ferocious tiger into letting himself be tied to a tree on the premise that the man would give him some of his wisdom, in a fable that tells how the tiger got his stripes.
2.5
K-3
K-3
460L
Keywords: Folklore -- Vietnam; Tigers -- Folklore; Folklore -- Vietnam; Tigers -- Folklore; Folklore -- Vietnam; Tigers -- Folklore; Folklore